2003
DOI: 10.1016/s0140-6736(03)13412-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical progression and viral load in a community outbreak of coronavirus-associated SARS pneumonia: a prospective study

Abstract: The consistent clinical progression, shifting radiological infiltrates, and an inverted V viral-load profile suggest that worsening in week 2 is unrelated to uncontrolled viral replication but may be related to immunopathological damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

106
2,421
30
88

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,249 publications
(2,679 citation statements)
references
References 15 publications
106
2,421
30
88
Order By: Relevance
“…In Hong Kong, a prospective study of 75 SARS cases demonstrated SARS-CoV IgG seroconversion in 70 (93%) cases by use of an in-house indirect IFA with acetone-fixed SARS-CoV-infected Vero cells, with antibodies detectable at a mean of 20 days (range, 11 to 28) after onset (9). This level of detection was similar to that in the same group's retrospective analysis of 50 cases, where all 32 patients with acute-and convalescent-phase sera demonstrated seroconversion or fourfold rises in SARS-CoV-specific antibody levels by IFA; 280 control sera were negative (8). SARS-CoVspecific antibodies have been detected by IFA in 94% (264 of 282) of SARS cases in combined series (4).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…In Hong Kong, a prospective study of 75 SARS cases demonstrated SARS-CoV IgG seroconversion in 70 (93%) cases by use of an in-house indirect IFA with acetone-fixed SARS-CoV-infected Vero cells, with antibodies detectable at a mean of 20 days (range, 11 to 28) after onset (9). This level of detection was similar to that in the same group's retrospective analysis of 50 cases, where all 32 patients with acute-and convalescent-phase sera demonstrated seroconversion or fourfold rises in SARS-CoV-specific antibody levels by IFA; 280 control sera were negative (8). SARS-CoVspecific antibodies have been detected by IFA in 94% (264 of 282) of SARS cases in combined series (4).…”
supporting
confidence: 69%
“…SARSCoV RT-PCR has only a modest sensitivity of approximately 30% on a single respiratory sample collected early in the illness (8), although its sensitivity improves if serial samples are collected in the first 2 weeks, since maximal viral shedding occurs 7 to 10 days after onset (4,8). The most reliable laboratory test for the confirmation of SARS is detection of SARS-CoVspecific antibodies (4,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These samples were primarily collected early in the outbreak when the recommendation for convalescent-phase serum collection was set for >21 days after exposure. Evidence from other studies shows that most case-patients case will seroconvert by day 20 ( 13 ). Although this ELISA is currently used as a standard criterion and has unknown sensitivity, a similar assay has been reported to have an estimated sensitivity of approximately 93%, based on clinical case definitions for probable SARS ( 13 ).…”
Section: Discussionmentioning
confidence: 97%
“…In Singapore, five patients were identified early in the epidemic who had infected > 10 contacts each ( 10 ). The timing of exposure to ill patients also is critical; patients may be most infectious in the second week of illness, as some data suggest peak viral shedding occurs at day 10 ( 13 ). Additionally, descriptive data suggest that severely ill patients may spread virus more efficiently, particularly if they are coughing or vomiting ( 12 ).…”
Section: Discussionmentioning
confidence: 99%